A flame-retardant insulation protective film and a method for preparing the same

CN122958835APending Publication Date: 2026-10-23SHENZHEN DANJIANG IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129497.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,PET属可燃物,阻燃与导热性能明显不足,难以满足锂电池组在高功率充放电工况下对散热与防火安全的双重需求

Benefits of technology

本发明利用氮化铝晶须的桥联作用与六方氮化硼纳米片的片层铺展作用协同构建导热网络,使导热路径由单一颗粒点接触转变为晶须桥联和片层面接触相结合的复合导热通路,不仅可显著降低局部热积聚,而且在高温或燃烧条件下,氮化铝晶须和六方氮化硼纳米片可作为无机骨架,提升炭层的连续性和抗开裂能力;同时,含磷硅铝组分形成的复合阻隔结构能够进一步稳定导热填料网络,降低导热结构粉化脱落的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958835A_ABST
    Figure CN122958835A_ABST
Patent Text Reader

Abstract

The application relates to the field of PET technology, in particular to a flame-retardant insulating protective film and a preparation method thereof. The raw materials of the flame-retardant insulating protective film include, by mass fraction, 80-120 parts of polyethylene terephthalate, 10-16 parts of aluminum diethyl phosphinate, 4-8 parts of melamine polyphosphate, 1-2 parts of ODOPB flame retardant, 1-3 parts of methylphenyl silicone resin, 2-5 parts of boehmite, 25-45 parts of heat-conducting filler, 4-8 parts of GMA toughening agent, 0.4-1.2 parts of trisglycidyl isocyanurate, 0.2-0.6 parts of hydrolysis-resistant agent, 0.3-0.8 parts of antioxidant, and 0.3-1 part of processing aid. The application effectively reduces the adverse effects of corrosive flue gas and halogen-containing decomposition products on the safety of battery module metal parts, electrical connecting parts and personnel, and is suitable for being used as an external insulating protective film of a new energy automobile power battery pack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of PET material technology, and in particular to a flame-retardant insulating protective film and its preparation method. Background Technology

[0002] In recent years, with economic development and improved living standards, automobiles have become a major mode of transportation. However, the environmental pollution and energy crisis caused by traditional fuel vehicles are becoming increasingly serious, making clean new energy vehicles, represented by electric vehicles, the mainstream direction of industry development.

[0003] Electric vehicles are powered by electricity, with lithium-ion battery packs serving as the core energy supply component. The performance, stability, and safety of these battery packs directly determine the reliability and market prospects of the entire vehicle. Electric vehicles face complex operating conditions during operation, including high-speed movement, severe vibration, high temperatures, and rapid charging and discharging. Lithium-ion battery packs are highly susceptible to various risks, seriously threatening the safety of occupants. Therefore, effectively protecting lithium-ion battery packs is crucial to ensuring the safe operation of new energy vehicles.

[0004] Currently, wrapping lithium battery packs with high-strength composite materials is a common protective measure. Polyethylene terephthalate (PET) has been used in the field of lithium battery pack insulation protection due to its excellent mechanical properties, corrosion resistance, ease of processing, and outstanding electrical insulation, as well as its ability to maintain good physical and mechanical properties over a wide temperature range and a long-term operating temperature of up to 120℃. However, PET is a flammable material, and its flame retardant and thermal conductivity are significantly insufficient, making it difficult to meet the dual requirements of heat dissipation and fire safety for lithium battery packs under high-power charging and discharging conditions.

[0005] Therefore, enhancing the flame retardant and thermal conductivity properties of PET and providing a protective film material that combines flame retardancy, thermal conductivity, and insulation is of great significance for improving the safety performance of lithium battery packs and promoting the reliable development of new energy vehicles. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a flame-retardant insulating protective film and its preparation method.

[0007] A flame-retardant insulating protective film, the raw materials of which, by weight, include: 80-120 parts polyethylene terephthalate, 10-16 parts aluminum diethylphosphinate, 4-8 parts melamine polyphosphate, 1-2 parts ODOPB flame retardant, 1-3 parts methylphenyl silicone resin, 2-5 parts boehmite, 25-45 parts thermally conductive filler, 4-8 parts GMA toughening agent, 0.4-1.2 parts triglycidyl isocyanurate, 0.2-0.6 parts hydrolysis inhibitor, 0.3-0.8 parts antioxidant, and 0.3-1 parts processing aid.

[0008] Preferably, the intrinsic viscosity of polyethylene terephthalate is 0.65-0.85 dL / g.

[0009] Preferably, the GMA-type toughening agent is an ethylene-glycidyl methacrylate copolymer.

[0010] Preferably, the anti-hydrolysis agent is a carbodiimide-based anti-hydrolysis agent.

[0011] Preferably, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 0.8-1.2:1-1.5.

[0012] Preferably, the processing aid is pentaerythritol stearate and / or silicone powder.

[0013] Preferably, the thermally conductive filler is prepared by the following steps: aluminum nitride whiskers are treated with oxygen plasma for 2-6 minutes to obtain surface-activated aluminum nitride whiskers; hexagonal boron nitride nanosheets are coated with dopamine and dispersed in an ethanol aqueous solution, an aminosilane coupling agent is added, and the mixture is ultrasonically treated at 60-70℃ for 1-3 hours; surface-activated aluminum nitride whiskers and epoxy silane coupling agent are added, and the mixture is stirred at 40-45℃ for 10-30 minutes; the mixture is then filtered, washed, and vacuum dried.

[0014] Preferably, the mass ratio of aluminum nitride whiskers, hexagonal boron nitride nanosheets, aminosilane coupling agent, and epoxysilane coupling agent is 18-28:6-12:1-2:0.1-1.

[0015] Preferably, the aluminum nitride whiskers have an average diameter of 0.2-1.5 μm and an average length of 5-30 μm; the hexagonal boron nitride nanosheets have a D50 of 0.5-5 μm.

[0016] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Mix polyethylene terephthalate, GMA toughening agent, triglycidyl isocyanurate, anti-hydrolysis agent, antioxidant and processing aid for 3-5 minutes, then add aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler and mix for 3-6 minutes to obtain a premix. S2. The premixed material is melt-extruded and granulated, then cooled, granulated, dried at 120-130℃ for 3-5 hours, and then extruded and cast into a film. S3. The cast film is preheated at 90-120℃, oriented by 1.2-2.5 times longitudinal traction, heat-set at 180-220℃ for 10-60s, and then cooled and wound up.

[0017] Preferably, in S2, a twin-screw extruder is used for melt extrusion granulation; the length-to-diameter ratio of the twin-screw extruder is 40-52:1, and the screw speed is 180-350 r / min; the temperatures of each zone are as follows: Zone 1 225-235℃, Zone 2 240-250℃, Zone 3 250-260℃, Zone 4 255-265℃, Zone 5 260-270℃, and the die head 260-270℃.

[0018] Preferably, in S2, the dried granules are extruded and cast into a film through a T-die; the casting temperature is 255-270℃, the die temperature is 260-270℃, the cooling roller temperature is 25-45℃, the traction speed is 1-8m / min, and the die lip gap is 0.15-0.80mm.

[0019] Compared with existing technologies, the present invention has the following advantages: This invention utilizes the bridging effect of aluminum nitride whiskers and the layer-spreading effect of hexagonal boron nitride nanosheets to synergistically construct a thermally conductive network. This transforms the thermal conductivity path from a single particle point contact to a composite thermal conductivity pathway combining whisker bridging and layer-spreading contact. This not only significantly reduces local heat accumulation, but also, under high-temperature or combustion conditions, the aluminum nitride whiskers and hexagonal boron nitride nanosheets can serve as an inorganic framework, improving the continuity and crack resistance of the carbon layer. Simultaneously, the composite barrier structure formed by the phosphorus-silicon-aluminum components can further stabilize the thermally conductive filler network and reduce the risk of pulverization and detachment of the thermally conductive structure.

[0020] Methylphenyl silicone resin contains a Si-O-Si main chain structure, which forms an inorganic barrier residue at high combustion temperatures. Boehmite dehydrates at high combustion temperatures to form an inorganic phase containing aluminum oxide. Methylphenyl silicone resin, boehmite, aluminum diethylphosphinate, melamine polyphosphate, and ODOPB flame retardant work synergistically to form a composite barrier carbon layer containing phosphorus, silicon, and aluminum, which synergistically inhibits the transfer of heat, oxygen, and combustible pyrolysis products.

[0021] This invention eliminates the need for halogenated flame retardants and antimony trioxide, effectively reducing the adverse effects of corrosive fumes and halogenated decomposition products on battery module metal parts, electrical connectors, and personnel safety. It is more suitable as an external insulating protective film for power battery packs in new energy vehicles. Attached Figure Description

[0022] Figure 1 This is a comparison chart of the tensile strength and thermal conductivity of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2.

[0023] Figure 2 The graph shows a comparison of the maximum puncture force and dart impact damage mass of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2. Detailed Implementation

[0024] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.

[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0026] The polyethylene terephthalate used below is sourced from DuPont, USA, with the brand name FR530CS WT597; it should be dried at 120-140℃ for 4-6 hours before use.

[0027] The ethylene-glycidyl methacrylate copolymer used below is sourced from Sumitomo Chemical, brand name BF-E; it should be dried at 70-90°C for 1-3 hours before use.

[0028] The aluminum diethylphosphonate, melamine polyphosphate, ODOPB flame retardant, methylphenyl silicone resin, and boehmite used below should be dried at 80-110℃ for 2-4 hours before use. The antioxidants used below are composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 0.8-1.2:1-1.5. The aluminum nitride whiskers used below have an average diameter of 1 μm and an average length of 10 μm. The hexagonal boron nitride nanosheets used below have a D50 of 2 μm.

[0029] The specific process for dopamine coating of hexagonal boron nitride nanosheets is as follows: hexagonal boron nitride nanosheets are added to Tris buffer solution with pH 8.5-9, stirred at 400 r / min for 20 min, sonicated at 45 kHz for 10 min, dopamine hydrochloride is added, stirred at 25℃ for 8 h, centrifuged, washed, and vacuum dried; wherein the weight ratio of hexagonal boron nitride nanosheets, dopamine hydrochloride, and Tris buffer solution is 1:0.02:20.

[0030] In the oxygen plasma treatment process described below, the oxygen flow rate is 80 sccm, the chamber pressure is 75 Pa, and the radio frequency power is 200 W.

[0031] Example 1: A flame-retardant insulating protective film, the raw materials of which include: 80g polyethylene terephthalate, 10g aluminum diethylphosphinate, 4g melamine polyphosphate, 2g ODOPB flame retardant, 1g methylphenyl silicone resin, 2g boehmite, 25g thermally conductive filler, 4g ethylene-glycidyl methacrylate copolymer, 0.4g triglycidyl isocyanurate, 0.2g carbodiimide, 0.3g antioxidant, and 0.3g pentaerythritol stearate.

[0032] The thermally conductive filler was prepared using the following steps: 18g of aluminum nitride whiskers were treated with oxygen plasma for 3 minutes to obtain surface-activated aluminum nitride whiskers; 6g of hexagonal boron nitride nanosheets coated with dopamine were dispersed in 50g of 70% ethanol aqueous solution, 1g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 60℃ for 1 hour. Then, surface-activated aluminum nitride whiskers and 0.1g of epoxysilane coupling agent were added, and the mixture was stirred at 40℃ for 30 minutes. The mixture was then filtered, washed, and vacuum dried.

[0033] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 300 r / min for 3 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler are added and mixed at 600 r / min for 3 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 40:1, a screw speed of 180 r / min, and a vacuum degree of -0.08 MPa. The temperatures of each zone are as follows: Zone 1 225℃, Zone 2 240℃, Zone 3 250℃, Zone 4 255℃, Zone 5 260℃, and the die head 260℃. The extruded granules are cooled, pelletized, and dried at 120℃ for 3 hours. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 255℃, the die head temperature is 260℃, the cooling roller temperature is 25℃, the traction speed is 1 m / min, and the die lip gap is 0.15 mm. S3. The resulting film is preheated at 90°C, oriented by 1.2 times longitudinal traction, heat-set at 180°C for 10 seconds, and then cooled and wound up.

[0034] Example 2: A flame-retardant insulating protective film, the raw materials of which include: 120g polyethylene terephthalate, 16g aluminum diethylphosphinate, 8g melamine polyphosphate, 1g ODOPB flame retardant, 3g methylphenyl silicone resin, 5g boehmite, 45g thermally conductive filler, 8g ethylene-glycidyl methacrylate copolymer, 1.2g triglycidyl isocyanurate, 0.6g carbodiimide, 0.8g antioxidant, and 1g pentaerythritol stearate.

[0035] The thermally conductive filler was prepared using the following steps: 28g of aluminum nitride whiskers were treated with oxygen plasma for 6 minutes to obtain surface-activated aluminum nitride whiskers; 12g of hexagonal boron nitride nanosheets coated with dopamine were dispersed in 80g of 80% ethanol aqueous solution, 2g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 70℃ for 3 hours. Then, surface-activated aluminum nitride whiskers and 1g of epoxysilane coupling agent were added, and the mixture was stirred at 45℃ for 10 minutes. The mixture was then filtered, washed, and vacuum dried.

[0036] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 600 r / min for 5 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler are added and the mixture is continued at 1000 r / min for 6 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 52:1, a screw speed of 350 r / min, and a vacuum degree of -0.095 MPa. The temperatures of each zone are as follows: Zone 1 235℃, Zone 2 250℃, Zone 3 260℃, Zone 4 265℃, Zone 5 270℃, and the die head 270℃. The extruded granules are cooled, pelletized, and dried at 130℃ for 5 hours. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 270℃, the die head temperature is 270℃, the cooling roller temperature is 45℃, the traction speed is 8 m / min, and the die lip gap is 0.55 mm. S3. The resulting film is preheated at 120°C, oriented by 2.5 times longitudinal traction, heat-set at 220°C for 60 seconds, and then cooled and wound up.

[0037] Example 3: A flame-retardant insulating protective film, the raw materials of which include: 90g polyethylene terephthalate, 15g aluminum diethylphosphinate, 5g melamine polyphosphate, 1.5g ODOPB flame retardant, 1.5g methyl phenyl silicone resin, 4g boehmite, 30g thermally conductive filler, 7g ethylene-glycidyl methacrylate copolymer, 0.6g triglycidyl isocyanurate, 0.5g carbodiimide, 0.5g antioxidant, and 0.8g pentaerythritol stearate.

[0038] The thermally conductive filler was prepared using the following steps: 20g of aluminum nitride whiskers were treated with oxygen plasma for 5 min to obtain surface-activated aluminum nitride whiskers; 10g of hexagonal boron nitride nanosheets coated with dopamine were dispersed in 60g of 85% ethanol aqueous solution, 1.2g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 68℃ for 1.5h. Then, surface-activated aluminum nitride whiskers and 0.7g of epoxysilane coupling agent were added, and the mixture was stirred at 40℃ for 10 min. The mixture was then filtered, washed, and vacuum dried.

[0039] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 400 r / min for 4 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler are added and mixed at 900 r / min for 4 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 50:1, a screw speed of 200 r / min, and a vacuum degree of -0.090 MPa. The temperatures of each zone are as follows: Zone 1 228℃, Zone 2 242℃, Zone 3 252℃, Zone 4 258℃, Zone 5 262℃, and the die head 262℃. The extruded granules are cooled, pelletized, and dried at 122℃ for 3.5 h. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 260℃, the die head temperature is 262℃, the cooling roller temperature is 30℃, the traction speed is 6 m / min, and the die lip gap is 0.25 mm. S3. The resulting film is preheated at 110°C, oriented by 1.5 times longitudinal traction, heat-set at 210°C for 20 seconds, and then cooled and wound up.

[0040] Example 4: A flame-retardant insulating protective film, the raw materials of which include: 110g polyethylene terephthalate, 11g aluminum diethylphosphinate, 7g melamine polyphosphate, 1.5g ODOPB flame retardant, 2.5g methyl phenyl silicone resin, 3g boehmite, 40g thermally conductive filler, 5g ethylene-glycidyl methacrylate copolymer, 1g triglycidyl isocyanurate, 0.3g carbodiimide, 0.7g antioxidant, and 0.4g pentaerythritol stearate.

[0041] The thermally conductive filler was prepared using the following steps: 26g of aluminum nitride whiskers were treated with oxygen plasma for 4 min to obtain surface-activated aluminum nitride whiskers; 8g of hexagonal boron nitride nanosheets coated with dopamine were dispersed in 70g of 95% ethanol aqueous solution, 1.8g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 62℃ for 2.5h. Then, surface-activated aluminum nitride whiskers and 0.3g of epoxysilane coupling agent were added, and the mixture was stirred at 40℃ for 10 min. The mixture was then filtered, washed, and vacuum dried.

[0042] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 500 r / min for 4 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler are added and the mixture is continued at 700 r / min for 5 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 42:1, a screw speed of 300 r / min, and a vacuum degree of -0.085 MPa. The temperatures of each zone are as follows: Zone 1 232℃, Zone 2 248℃, Zone 3 258℃, Zone 4 262℃, Zone 5 268℃, and the die head 268℃. The extruded granules are cooled, pelletized, and dried at 128℃ for 4.5 h. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 265℃, the die head temperature is 268℃, the cooling roller temperature is 40℃, the traction speed is 2 m / min, and the die lip gap is 0.6 mm. S3. The resulting film is preheated at 100℃, oriented by 2.2 times longitudinal traction, heat-set at 190℃ for 50s, and then cooled and wound up.

[0043] Example 5: A flame-retardant insulating protective film, the raw materials of which include: 100g polyethylene terephthalate, 12g aluminum diethylphosphinate, 6g melamine polyphosphate, 1.5g ODOPB flame retardant, 2g methyl phenyl silicone resin, 3.5g boehmite, 35g thermally conductive filler, 6g ethylene-glycidyl methacrylate copolymer, 0.8g triglycidyl isocyanurate, 0.4g carbodiimide, 0.6g antioxidant, and 0.6g pentaerythritol stearate.

[0044] The thermally conductive filler was prepared using the following steps: 22g of aluminum nitride whiskers were treated with oxygen plasma for 4 min to obtain surface-activated aluminum nitride whiskers; 9g of hexagonal boron nitride nanosheets coated with dopamine were dispersed in 65g of 95% ethanol aqueous solution, 1.5g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 65℃ for 2 h. Then, surface-activated aluminum nitride whiskers and 0.5g of epoxysilane coupling agent were added, and the mixture was stirred at 40℃ for 10 min. The mixture was then filtered, washed, and vacuum dried.

[0045] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 450 r / min for 4 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methylphenyl silicone resin, boehmite and thermally conductive filler are added and mixed at 800 r / min for 4.5 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 46:1, a screw speed of 240 r / min, and a vacuum degree of -0.088 MPa. The temperatures of each zone are as follows: Zone 1 230℃, Zone 2 245℃, Zone 3 255℃, Zone 4 260℃, Zone 5 265℃, and the die head 265℃. The extruded granules are cooled, pelletized, and dried at 125℃ for 4 hours. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 262℃, the die head temperature is 265℃, the cooling roller temperature is 35℃, the traction speed is 4 m / min, and the die lip gap is 0.5 mm. S3. The resulting film is preheated at 105℃, oriented by twice the longitudinal traction, heat-set at 200℃ for 35s, and then cooled and wound up.

[0046] Comparative Example 1: A flame-retardant insulating protective film, the raw materials of which include: 100g polyethylene terephthalate, 12g aluminum diethylphosphinate, 6g melamine polyphosphate, 1.5g ODOPB flame retardant, 2g methyl phenyl silicone resin, 3.5g boehmite, 35g thermally conductive filler, 6g ethylene-glycidyl methacrylate copolymer, 0.8g triglycidyl isocyanurate, 0.4g carbodiimide, 0.6g antioxidant, and 0.6g pentaerythritol stearate.

[0047] The thermally conductive filler was prepared by the following steps: 22g of aluminum nitride whiskers and 9g of hexagonal boron nitride nanosheets were mixed evenly.

[0048] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 450 r / min for 4 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methylphenyl silicone resin, boehmite and thermally conductive filler are added and mixed at 800 r / min for 4.5 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 46:1, a screw speed of 240 r / min, and a vacuum degree of -0.088 MPa. The temperatures of each zone are as follows: Zone 1 230℃, Zone 2 245℃, Zone 3 255℃, Zone 4 260℃, Zone 5 265℃, and the die head 265℃. The extruded granules are cooled, pelletized, and dried at 125℃ for 4 hours. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 262℃, the die head temperature is 265℃, the cooling roller temperature is 35℃, the traction speed is 4 m / min, and the die lip gap is 0.5 mm. S3. The resulting film is preheated at 105℃, oriented by twice the longitudinal traction, heat-set at 200℃ for 35s, and then cooled and wound up.

[0049] Comparative Example 2: A flame-retardant insulating protective film, the raw materials of which include: 100g polyethylene terephthalate, 12g aluminum diethylphosphinate, 6g melamine polyphosphate, 1.5g ODOPB flame retardant, 2g methylphenyl silicone resin, 3.5g boehmite, 35g thermally conductive filler, 6g ethylene-glycidyl methacrylate copolymer, 0.8g triglycidyl isocyanurate, 0.4g carbodiimide, 0.6g antioxidant, and 0.6g pentaerythritol stearate.

[0050] The thermally conductive filler was prepared using the following steps: 22g of aluminum nitride whiskers were treated with oxygen plasma for 4 min to obtain surface-activated aluminum nitride whiskers; 9g of aluminum nitride whiskers were coated with dopamine and dispersed in 65g of 95% ethanol aqueous solution, 1.5g of aminosilane coupling agent was added, and the mixture was ultrasonically treated at 65℃ for 2 h; then, surface-activated aluminum nitride whiskers and 0.5g of epoxysilane coupling agent were added, and the mixture was stirred at 40℃ for 10 min; the mixture was then filtered, washed, and vacuum dried.

[0051] The specific process for coating aluminum nitride whiskers with dopamine is the same as that for coating hexagonal boron nitride nanosheets with dopamine.

[0052] The preparation method of the above-mentioned flame-retardant insulating protective film includes the following steps: S1. Polyethylene terephthalate, ethylene-glycidyl methacrylate copolymer, triglycidyl isocyanurate, carbodiimide, antioxidant and pentaerythritol stearate are added to a mixer and mixed at 450 r / min for 4 min. Then, aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methylphenyl silicone resin, boehmite and thermally conductive filler are added and mixed at 800 r / min for 4.5 min to obtain a premix. S2. The premixed material is added to a twin-screw extruder for melt blending, vacuum degassing, and extrusion granulation. The twin-screw extruder has a length-to-diameter ratio of 46:1, a screw speed of 240 r / min, and a vacuum degree of -0.088 MPa. The temperatures of each zone are as follows: Zone 1 230℃, Zone 2 245℃, Zone 3 255℃, Zone 4 260℃, Zone 5 265℃, and the die head 265℃. The extruded granules are cooled, pelletized, and dried at 125℃ for 4 hours. The dried granules are then added to a casting extrusion device and extruded through a T-die to form a film. The casting temperature is 262℃, the die head temperature is 265℃, the cooling roller temperature is 35℃, the traction speed is 4 m / min, and the die lip gap is 0.5 mm. S3. The resulting film is preheated at 105℃, oriented by twice the longitudinal traction, heat-set at 200℃ for 35s, and then cooled and wound up.

[0053] The thickness of the flame-retardant insulating protective film obtained in Example 5 and Comparative Examples 1-2 was measured, and the thickness of all three was 75±5μm.

[0054] The tensile strength of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2 was determined in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets".

[0055] The thermal conductivity of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2 was determined in accordance with GB / T 42919.3-2023 "Determination of thermal conductivity and thermal diffusivity of plastics - Part 3: Temperature wave analysis".

[0056] like Figure 1 As shown, the flame-retardant insulating protective film obtained in Example 5 has the highest tensile strength and thermal conductivity, which are significantly better than those of the comparative example.

[0057] The maximum puncture force of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2 was determined with reference to GB / T 37841-2019 "Test Method for Puncture Resistance of Plastic Films and Sheets".

[0058] The dart impact failure mass of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2 was determined with reference to GB / T 9639.1-2008 "Test methods for impact resistance of plastic films and sheets - free-falling dart method - Part 1: step method".

[0059] like Figure 2 As shown, the flame-retardant insulating protective film obtained in Example 5 has the highest maximum puncture force and dart impact damage quality, which is significantly better than the comparative example.

[0060] The flame retardancy ratings of the flame-retardant insulating protective films obtained in Example 5 and Comparative Examples 1-2 were determined with reference to the vertical burning method for thin materials in UL94. All three films achieved a flame retardancy rating of VTM-0.

[0061] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope, and without requiring unnecessary experiments. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including changes made using conventional techniques known in the art that depart from the scope disclosed herein.

Claims

1. A flame-retardant insulating protective film, characterized in that, The raw materials, by weight, include: 80-120 parts polyethylene terephthalate, 10-16 parts aluminum diethylphosphinate, 4-8 parts melamine polyphosphate, 1-2 parts ODOPB flame retardant, 1-3 parts methyl phenyl silicone resin, 2-5 parts boehmite, 25-45 parts thermally conductive filler, 4-8 parts GMA toughening agent, 0.4-1.2 parts triglycidyl isocyanurate, 0.2-0.6 parts anti-hydrolysis agent, 0.3-0.8 parts antioxidant, and 0.3-1 parts processing aid.

2. The flame-retardant insulating protective film according to claim 1, characterized in that, The intrinsic viscosity of polyethylene terephthalate is 0.65-0.85 dL / g.

3. The flame-retardant insulating protective film according to claim 1, characterized in that, GMA-type toughening agent is an ethylene-glycidyl methacrylate copolymer.

4. The flame-retardant insulating protective film according to claim 1, characterized in that, The anti-hydrolysis agent is a carbodiimide-based anti-hydrolysis agent.

5. The flame-retardant insulating protective film according to claim 1, characterized in that, The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 0.8-1.2:1-1.

5.

6. The flame-retardant insulating protective film according to claim 1, characterized in that, The processing aids are pentaerythritol stearate and / or silicone powder.

7. The flame-retardant insulating protective film according to claim 1, characterized in that, The thermally conductive filler is prepared by the following steps: aluminum nitride whiskers are treated with oxygen plasma for 2-6 minutes to obtain surface-activated aluminum nitride whiskers; hexagonal boron nitride nanosheets are coated with dopamine and dispersed in an ethanol aqueous solution, aminosilane coupling agent is added, and ultrasonic treatment is carried out at 60-70℃ for 1-3 hours; surface-activated aluminum nitride whiskers and epoxysilane coupling agent are added, and stirring is carried out at 40-45℃ for 10-30 minutes; then the mixture is filtered, washed, and vacuum dried.

8. The flame-retardant insulating protective film according to claim 1, characterized in that, The mass ratio of aluminum nitride whiskers, hexagonal boron nitride nanosheets, aminosilane coupling agent, and epoxysilane coupling agent is 18-28:6-12:1-2:0.1-1.

9. A method for preparing a flame-retardant insulating protective film as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Mix polyethylene terephthalate, GMA toughening agent, triglycidyl isocyanurate, anti-hydrolysis agent, antioxidant and processing aid for 3-5 minutes, then add aluminum diethylphosphinate, melamine polyphosphate, ODOPB flame retardant, methyl phenyl silicone resin, boehmite and thermally conductive filler and mix for 3-6 minutes to obtain a premix. S2. The premixed material is melt-extruded and granulated, then cooled, granulated, dried at 120-130℃ for 3-5 hours, and then extruded and cast into a film. S3. The cast film is preheated at 90-120℃, oriented by 1.2-2.5 times longitudinal traction, heat-set at 180-220℃ for 10-60s, and then cooled.

10. The method for preparing the flame-retardant insulating protective film according to claim 9, characterized in that, In S2, a twin-screw extruder is used for melt extrusion granulation; the length-to-diameter ratio of the twin-screw extruder is 40-52:1, and the screw speed is 180-350 r / min; the temperatures of each zone are as follows: Zone 1 225-235℃, Zone 2 240-250℃, Zone 3 250-260℃, Zone 4 255-265℃, Zone 5 260-270℃, and the die head 260-270℃.